2013
DOI: 10.1080/10402004.2013.843738
|View full text |Cite
|
Sign up to set email alerts
|

Cage Friction in High-Speed Spindle Bearings

Abstract: Friction-induced heat is one of the main reasons for the upper speed limit of high-speed angular contact ball bearings (spindle bearings). One source of friction inside the bearing is the cage. In this article, it is shown through experimental results that the frictional losses due to the cage are of significant magnitude. Based on measurements, a new, simple calculation model is proposed to estimate the cage induced frictional losses in spindle bearings under high rotational speed with minimal lubrication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…For detailed analysis of the cage friction torque, readers may refer to Brecher et al. 25 This section presents the friction torque formulas for all the torque components. Radial load or angular misalignment can cause a variation in the contact loads in rolling elements.…”
Section: Calculation Methods For Acbb Running Torque With Angular Misamentioning
confidence: 99%
See 3 more Smart Citations
“…For detailed analysis of the cage friction torque, readers may refer to Brecher et al. 25 This section presents the friction torque formulas for all the torque components. Radial load or angular misalignment can cause a variation in the contact loads in rolling elements.…”
Section: Calculation Methods For Acbb Running Torque With Angular Misamentioning
confidence: 99%
“…4 For a tapered roller bearing lubricated using an oil bath, Liebrecht et al 24 reported that the cage drag torque is less than 1% of the total friction torque. For detailed analysis of the cage friction torque, readers may refer to Brecher et al 25 This section presents the friction torque formulas for all the torque components. Radial load or angular misalignment can cause a variation in the contact loads in rolling elements.…”
Section: Acbb Is Expressed By Equation (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Savas xkan and Maleki 15 performed experiments to investigate the friction and wear properties of Zn-25Al-based bearing alloys. Brecher et al 16 investigated the effects of cage friction in the high-speed spindle bearings and proved that the frictional torque caused by cage friction could not be neglected in the analysis of bearing friction resistance. With respect to the investigations on the bearing with defects, Shaha et al 17 carried out a lot of experiments and indicated the correlation between the frictional torques and the different size defects.…”
Section: School Of Mechanical Electronic and Information Engineering Cmentioning
confidence: 99%